The managed economy - Reagan, Michael D. (New York : Oxford University Press, 1963)
This book elaborates a theme that flows from a fact and a political belief. In this book Reagan shows that the source of the complication that we face in trying to disentangle reality from ideology is that the automatic market economy of the 19th century has been done to death, and displaced by a managerial oligarchy whose conscious choices now weigh heavily in the allocation of resources. (3z(BThe rise of this managed economy,(3y (Bin Reagan's words, (3z(Breunites politics and economics . . . into political economy,(3y (Bnot because government intervention has increased but because the important decisions, even in the private sector, are individual ones embodying entirely personal values.s
Includes index.
Includes bibliographical notes": p. 269-279.
rpm 01/11/2017
Loans
Keywords: Big business; Industrial policy; Free enterprise; United States